The Adaptation of a Neuroendoscopic Sheath to a Leksell Stereotactic Frame to Make it Suitable for Approaching Small Ventricles: A Technical Note - Kitai, Ryuheki; Nakano, Kotaro; Hashimoto, Norichika; Arishima, Hidetaka; Yamauchi, Takahiro; Higashino, Yoshifumi; Takeuchi, Hiroaki; Kikuta, Ken-Ichiro (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Efficient endoscopic surgery in cases involving small ventricles is difficult but possible. The authors describe a neuroendoscopic sheath that has been improved to make it suitable for use with a Leksell stereotactic frame, which enabled us to accurately insert a stereotactic needle into the small ventricle and provided an adequate surgical corridor. A biopsy was performed on a 6-year-old girl who had a primary central nervous system lymphoma in the pineal body without hydrocephalus.
Keywords: neuroendoscope; stereotactic; sheath